If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6y + -10 + -3y + 6 = 0 Reorder the terms: -10 + 6 + 6y + -3y = 0 Combine like terms: -10 + 6 = -4 -4 + 6y + -3y = 0 Combine like terms: 6y + -3y = 3y -4 + 3y = 0 Solving -4 + 3y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 3y = 0 + 4 Combine like terms: -4 + 4 = 0 0 + 3y = 0 + 4 3y = 0 + 4 Combine like terms: 0 + 4 = 4 3y = 4 Divide each side by '3'. y = 1.333333333 Simplifying y = 1.333333333
| 9+4q=11+3q | | (-3u/v^3)^2 | | (2-a)(5z-7)=0 | | x/3-4=x-7 | | -4a+2=4a+82 | | e/-6=4 | | -7x+10=-3x+22 | | (72-x)=180 | | 5[7-5(-2x-9)]=50x+260 | | 6-2z=2z-10 | | (4x+32)=180 | | 20-1/10d=16 | | 5y+140=7x | | 22.27/x=4.16 | | 3x+2x^2-8x+6x^2= | | 22.27*x=4.16 | | x+22=34 | | 15=2x+10 | | x+22=33 | | 22.27*x=22.27 | | -2e^3x+19=3 | | 5y=7x-140 | | -x^2+6x=-1 | | 154/22 | | 11-3h+9=-8 | | 4x+1=2x+29 | | 3x-4=5x+9 | | https://www.mhcitts.com/images/test/53_1_8s.jpg | | 3x-7=6x-2 | | 165x+2771=7721 | | 2x(-5)=6x^2-11x | | 4/5x-3/4y=-10 |